2022
DOI: 10.18240/ijo.2022.08.03
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis to identify potential gene changes induced by dexamethasone in the trabecular meshwork

Abstract: AIM: To investigate potential gene changes in trabecular meshwork (TM) induced by dexamethasone (DEX) in steroid-induced glaucoma (SIG). METHODS: The expression data of 24 cases from a public functional genomics data were sorted to identify the mechanisms of action of DEX on the TM. The relationships of the differentially expressed genes (DEGs) were enriched using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. In addition, the hub genes were screened by the Search Tool for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The prolonged action of steroids within the vitreous is especially notable for sustained-release implants such as Iluvien and Retisert, which deliver fluocinolone acetonide intraocularly for up to 36 months 23. While the exact mechanism of steroid-induced glaucoma is not yet fully elucidated, corticosteroids are hypothesised to interact with various enzymes and cytoskeletal components within the trabecular meshwork to cause increased aqueous outflow resistance and therefore elevated IOP 2 3. Studies have demonstrated that corticosteroids can lead to microstructure alterations within the trabecular meshwork through the upregulation of myocilin and through binding to glucocorticoid receptor beta 24 25.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prolonged action of steroids within the vitreous is especially notable for sustained-release implants such as Iluvien and Retisert, which deliver fluocinolone acetonide intraocularly for up to 36 months 23. While the exact mechanism of steroid-induced glaucoma is not yet fully elucidated, corticosteroids are hypothesised to interact with various enzymes and cytoskeletal components within the trabecular meshwork to cause increased aqueous outflow resistance and therefore elevated IOP 2 3. Studies have demonstrated that corticosteroids can lead to microstructure alterations within the trabecular meshwork through the upregulation of myocilin and through binding to glucocorticoid receptor beta 24 25.…”
Section: Discussionmentioning
confidence: 99%
“… 23 While the exact mechanism of steroid-induced glaucoma is not yet fully elucidated, corticosteroids are hypothesised to interact with various enzymes and cytoskeletal components within the trabecular meshwork to cause increased aqueous outflow resistance and therefore elevated IOP. 2 3 Studies have demonstrated that corticosteroids can lead to microstructure alterations within the trabecular meshwork through the upregulation of myocilin and through binding to glucocorticoid receptor beta. 24 25 Others have postulated that physical obstruction of the trabecular meshwork by glucocorticoid crystals contributes to reduced aqueous outflow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease is characterized by the death of retinal ganglion cells (RGC) [ 1 , 2 ]. Recent studies have demonstrated that microglia senescence aggravates the risk of neurodegenerative diseases [ 3 ], and reversing aging microglia can effectively protect neuronal function and prevent the occurrence of neurodegenerative diseases such as cognitive impairment in aged individuals [ 4 ]. The neural protective function of macroglia decreases with age, which strides toward retinal neurodegeneration, including primary glaucoma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%